Changes in Callosal Angle After Successful Endoscopic Third Ventriculostomy Procedure in Pediatric Patients - Tanrikulu, Bahattin; Ozek, M. Memet (TURKISH NEUROSURGICAL SOC, 2020)
AIM: To determine whether callosal angle (CA) measurement, a diagnostic and prognostic tool used for normal-pressure hydrocephalus in adults, is a reliable radiological parameter for evaluating endoscopic third ventriculostomy (ETV) outcomes in pediatric patients. MATERIAL and METHODS: Forty-seven pediatric patients with hydrocephalus who underwent successful EN in our clinic between 2011 and 2015 were included in this study. Preoperative and postoperative three-month CA, lateral ventricle frontal horn (LVFH) width, Evans' index (El), and frontal-occipital horn ratio (FOR) parameters were recorded, with changes analyzed using a paired-samples t-test. RESULTS: There were 29 male and 18 female patients included within the cohort. For mean preoperative values, LVFH width was 58.8 +/- 14.9 mm, El was 0.43 +/- 0.09, FOR was 0.51 +/- 0.74, and CA was 78.5 degrees +/- 36.4 degrees. Separately, for mean postoperative values, LVFH width was 54 +/- 14.2 mm, El was 0.39 +/- 0.09, FOR was 0.47 +/- 0.07, and CA was 104.5 degrees +/- 32.6 degrees. The CA was increased and the LVFH width, El, and FOR were decreased in all patients within three months after surgery. The postoperative three-month change in CA was higher than those observed in the other parameters. CONCLUSION: Changes in CA after successful EN were dramatically higher than those in the other ventricular parameters. For this reason, we suggest CA be used as a radiological criterion during early radiological follow-up of patients after ETV.
Keywords: Pediatric hydrocephalus; Callosal angle; Endoscopic third ventriculostomy